SPACA6-hosted miR-99b~125a~let-7e cluster shapes melanoma resistance by modulating mTOR-mediated immunosuppression - Vallacchi, Viviana; Lupoli, Gianpiero; Shahaj, Eriomina; Aloisi, Mariachiara; Bergamini, Stefano; Frigerio, Simona; De Cecco, Loris; Vergani, Barbara; Todoerti, Katia; Banfi, Cristina; Leone, Biagio Eugenio; Di Guardo, Lorenza; et al. (Frontiers in Immunology, 2026)
Genomic, non-genomic, and immune alterations contribute to melanoma resistance to BRAF and MEK inhibitors. Here, we investigated the role of the SPACA6-hosted miR-99b~125a~let-7e cluster in modulating inflammatory processes and therapy resistance. We found that miR-99b, miR-125a, and let-7e were upregulated in progressing tumors from treated melanoma patients compared with untreated lesions, and in patients with short response duration compared with long-term responders. Similarly, miR-99b~125a~let-7e expression levels were high in melanoma cell lines with acquired resistance to BRAF/MEK inhibitors, showing upregulation of immunosuppressive cytokines. Combined inhibition of miR-99b, miR-125a and let-7e during drug treatment reduced proliferation of resistant cells and decreased the expression of pro-inflammatory cytokines such as CCL2, IL6, and IL8. Conversely, enforced overexpression of these miRNAs in drug sensitive cells promoted resistance and enhanced cytokine transcripts. In silico miR-99b, miR-125a and let-7e target gene analysis uncovered GNAI1, ADCY1 and NR6A1 genes in lipid metabolism pathways linked to BRAF/MEK inhibitor resistance, which converge on the activation of the mTOR signaling, and show down-regulation in resistant cells and tumors. RNA-seq and proteomic profiling of 3D cultures of patient-derived melanoma explants demonstrated that inhibition of the miR-99b~125a~let-7e cluster reprogrammed the tumor microenvironment, enhancing immune activation and suppressing mTOR signaling. Together, these findings identify the SPACA6-hosted miR-99b~125a~let-7e cluster as a regulator of BRAF/MEK inhibitor resistance through promotion of tumor survival and of an immunosuppressive microenvironment. Targeting this miRNA cluster may provide novel therapeutic opportunities to overcome drug resistance in metastatic melanoma.